The influence of migration speed on cooperation in spatial games. (6th December 2017) - Li, Wen-Jing; Jiang, Luo-Luo; Gu, Changgui; Yang, Huijie
Abstract: Migration is a common phenomenon in human society which provides a person an opportunity to search for a new life from one area to another. In the framework of game theory, people may migrate to escape from a current adverse environment (evading defection). Since people may migrate at different speeds, it is interesting to figure out the influence of migration speed on the evolution of cooperative behavior. In an attempt to discover the influence, we propose here a model based on an adaptive migration mechanism. In this model, an individual migrates or updates his/her strategy asynchronously, which is tuned by migration frequency. Firstly, it is found that an appropriate migration speed may evoke an effective mechanism, which enables cooperators dominate even in highly adverse conditions. Secondly, we check how migration speed alters the paradigm of cooperation quantitatively in the conditions of different migration frequency. When migration frequency is high, cooperation is promoted only at a small migration speed. However, when migration frequency is low, cooperation is always promoted at any migration speed. In addition, we also investigated the influence of temptation to defect on cooperation for the case of different migration speeds and migration frequencies. Our results may provide a fresh perspective on the understanding of how human behavior affects cooperation.